Resolving local dynamics of dual ions at the nanoscale in electrochemically active materials. (December 2019) - Yu, Junxi; Huang, Boyuan; Li, Aolin; Duan, Shanshan; Jin, Hongyun; Ma, Ming; Ou, Yun; Xie, Shuhong; Liu, Yunya; Li, Jiangyu
Abstract: Electrochemical conversion is typically studied at macroscopic scale, and it is quite challenging to probe local electrochemistry at the nanoscale, especially those involving multiple ions. Through a series of atomic force microscopy experiments, we demonstrate that two competing ionic strains arising from molar volume changes and electrochemical dipoles in a dual-ion system can reveal themselves in distinct relaxation behavior, enabling us to decouple their respective contributions and thus measure local diffusivity along with activation energy. Using soda-lime float glass as a model system, we observe a fast relaxation corresponding to diffusion of Na + and a slow relaxation associated with electrochemical dipoles formed between Na + and non-bridging oxygen. Assisted by simulations, we determine the local diffusivity of 5.64 × 10 − 16 m 2 / s and activation energy of 0.55eV for Na + at 100 °C. The study provides a powerful tool to resolve local dynamics of dual ions, which can be applied to study a variety of complex energy conversion and storage systems. Graphical abstract: Image 1 Highlights: Local dynamics of competing ions in the electrochemically active dual-ion systems is resolved at the nanoscale. Relaxation behavior of dual-ion systems is rationalized by the competing Vegard strain and electrochemical dipole. Local diffusivity and activation energy are measured quantitative at the nanoscale, assisted by phase field simulation. The method can be applied to a wide range of energy materials and systems involving multiple ions.